Epidermal papilloma in dermatological practice. Clinical presentation and treatment - Borzęcki, Adam; Miturska, Renata; Szponar-Bojda, Anna; Raszewska-Famielec, Magdalena (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction . Although epidermal papillomas are a common problem in clinical practice, they are rarely confirmed by histopathological examination. In macroscopic examination these lesions are often misdiagnosed as fibromas, viral warts, linear verrucous epidermal nevi or condylomata acuminata. The recent publications discuss the problem of surgical removal of epidermal papillomas in the youngest. When lesions are localized in the orbital area or on the trunk the effects of surgical treatment are usually unsatisfactory. In contrast, laser therapy is a painless and well-tolerated procedure. Moreover, laser therapy usually is an outpatient procedure even if the lesions are extensive. This method enables one to obtain a satisfactory cosmetic effect and remains the treatment of choice for epidermal papillomas. Objective . Evaluation of frequency of keratopapilloma, papilloma digitatum and papilloma condylomatoides in the material of Med-Laser Center in Lublin and analysis of patients’ demographic data, lesions localization and macroscopic diagnoses. Material and methods . Retrospective analysis of 4986 results of histopathological examination performed in Med-Laser in Lublin in the years 2005-2012. Results. In 131 of 4986 (2.6%) lesions histopathological examinations revealed epidermal papilloma: 103 keratopapillomas, 20 papilloma digitatum and 8 papilloma condylomatoides. The most frequent lesions (2.0% of all removed lesions) were keratopapillomas. Conclusions . The results indicate that epidermal papillomas have a tendency to occur in elderly patients, particularly older than 60. The lesions are more often localized on the face, mostly on eyelids, forehead and temples. Papillomas localized in the anogenital area should be differentiated from condylomata acuminata.